Reinforcing cholera intervention through prediction-aided prevention - Akanda, Ali Shafqat; Jutla, Antarpreet S.; Gute, David M.; Evans, Timothy Grant; Islam, Shafqul (© 2012 Bulletin of the World Health Organization, 2017)
This article was published in the Bulletin of the World Health Organization [ © 2012 Bulletin of the World Health Organization ] and the definite version is available at : http://dx.doi.org/10.2471/BLT.11.092189 The Journal's website is at: http://www.who.int/bulletin/volumes/90/3/11-092189.pdf